Particle Image Velocimetry Analysis on the Liquid-Sediment Model - Zawawi M.H.; Ng F.C.; Abas M.A.; Azman A.; Hassan N.H. (Springer Science and Business Media Deutschland GmbH, 2023)
Flow of water; Flow visualization; High speed cameras; Image analysis; Liquids; Piles; Sediments; Velocimeters; Case-studies; Costal problem; Experimental approaches; Flow visualisation; Particle image velocimetry; Particle image velocimetry analysis; Problem-based; Sediment model; Sediment profiles; Simple++; Velocity measurement